Developing the Skills Training Sets for Career Subjects for Mathayomsuksa 2 Students by Inquiry-Based Teaching - Tubmarerng, Chainarin; Wanno, Chonlada; Chunangrong, Utaiwadee; Rueangkesom, Thanachai (Journal of Human and Society, Sisaket Rajabhat University, 2025)
This research aimed to 1) develop a skill training set for achievement career subjects to be effective according to the criteria of 80/80 2) to find the effectiveness index of the skill training set for achievement career subjects 3) to compare the academic achievement of Mathayomsuksa 2 students before and after studying. The populations were 34 students from two Mathayomsuksa 2 classes during the first semester of 2024. The sample group consisted of 23 Mathayomsuksa 2/1 students from Surinrachamongkhol School, selected by simple random sampling. The research instruments included the learning management plan, skill training set, pre- and post-study achievement test. The statistics used for data analysis were percentage, mean, standard deviation, t-test dependent E1/E2 and E.I. The research results found that 1) the efficiency of skill training set development for career subjects was 85.06/83.20, which was higher than the standard set 80/80 2) the effectiveness index of the skill training set for the Mathayomsuksa 2 students, the number of values ​​was 0.7200, which showed that the students had improved by 72.00 percent. 3) comparing the students' academic achievement using the skill training set, it was found that the academic achievement after studying was higher than before, with statistical significance at the .05 level.